Faktor-Faktor Penetapan Nisbah Bagi Hasil Tabungan Mudharabah Berjangka Studi di Baitul Maal Wat Tamwil (Bmt) Ugt Sidogiri Cabang Tanah Merah Bangkalan - sari kamalia aini (Journal of Islamic Business Law, 2018)
This research aims to determine the factor of determining the profit sharing ratio and the distribution of losses on mudharabah time deposits in Baitul Maal wat Tamwil (BMT) UGT Sidogiri Branch Tanah Merah Bangkalan. The type of reseacrh used is a kind of juridical empirical research. With a conceptual research approach that is descriptive qualitative. Data are collected through interviews and documentation. Data are analyzed by descriptive method. The result show that the determination of the profit sharing and the distibution of losses on mudharabah time deposits are not fully in accordance with the provisions of the mudharabah theory. First, in terms of determining the profit sharing ratio based on the agreement of both parties and done bay the process of bargaining, but in practice there is no bargaining process because it has been establishedby BMT UGT Sidogiri Center. Secondly, in the event that the share of loss is taken out of profit and if it exceeds the profits, it is taken from the capital stock, but in practice the loss sharing of BMT sets aside 20% of the remaining results of its business as a backup/solution when there is a loss or unforeseen event.